Retropharyngeal effusion secondary to calcific tendinitis of the longus colli muscle: A case report and brief review of the literature - Musharaf Khan, DO; Subtain Ali, MD; Dhairya A Lakhani, MD (Radiology Case Reports)
Calcification or ossification of the longus colli tendon is a rare and often underdiagnosed cause of acute neck pain, typically seen in middle-aged adults, especially women. This condition results from the deposition of calcium hydroxyapatite crystals in the tendon, causing an inflammatory or granulomatous response. Common symptoms include neck pain, painful swallowing, and fever. CT imaging is the preferred diagnostic tool, showing retropharyngeal and prevertebral effusions with minimal or no peripheral enhancement, often accompanied by calcifications in the superior fibers of the longus colli tendon. This condition can be mistaken for a retropharyngeal abscess, which requires more invasive management, such as drainage. In contrast, calcific tendinitis responds well to conservative treatment, including nonsteroidal anti-inflammatory drugs (NSAIDs). Here, we report a case of retropharyngeal effusion secondary to calcific tendinitis of the longus colli muscle, highlighting the importance of distinguishing it from other conditions, such as retropharyngeal abscess, to avoid unnecessary invasive treatments.